Gut Commensal Parabacteroides goldsteinii MTS01 Alters Gut Microbiota Composition and Reduces Cholesterol to Mitigate Helicobacter pylori-Induced Pathogenesis - Lai, Chih-Ho; Lin, Tzu-Lung; Huang, Mei-Zi; Li, Shiao-Wen; Wu, Hui-Yu; Chiu, Ya-Fang; Yang, Chia-Yu; Chiu, Cheng-Hsun; Lai, Hsin-Chih (Frontiers in Immunology, 2022)
Helicobacter pylori infection is closely associated with various gastrointestinal diseases and poses a serious threat to human health because of its increasing antimicrobial resistance. H. pylori has two major virulence factors, vacuolating cytotoxin A (VacA) and cytotoxin-associated gene A (CagA), that are involved in H. pylori-induced pathogenesis. Probiotics have recently been applied to aid in eradicating H. pylori infection and reduce the adverse effects of antibiotic-based therapies. Parabacteroides goldsteinii MTS01 is a novel, next generation probiotic (NGP) with functions that can alleviate specific diseases by altering the gut microbiota. However, the mechanism by which P. goldsteinii MTS01 exerts its probiotic effects against H. pylori infection remains to be elucidated. Our results showed that administration of P. goldsteinii MTS01 in mice altered the composition of the gut microbiota and significantly reduced serum cholesterol, which mitigated H. pylori-induced gastric inflammation. In addition, the pathogenic effects of H. pylori VacA and CagA in gastric epithelial cells were markedly abrogated by treatment with P. goldsteinii MTS01. These results indicate that P. goldsteinii MTS01 has anti-virulence factor functions, can help to modulate gut microbiota composition, and thus could be developed as a novel functional probiotic for reducing H. pylori-induced pathogenesis.